Political Parties and Climate Change Policy Implementation in Pakistan: Green Initiatives in Punjab, Sindh, and Khyber Pakhtunkhwa (2013–2018) - Sumaira Manzoor; Dr. Mussawar Hussain Bukhari (Journal for Social Science Archives, 2025)
Pakistan has been faced with severe climatic challenges which include deforestation and land degradation combined with susceptibility to ecological insecurity thus necessitating early and effective policy measures. The study was done to examine whether major political parties in Pakistan, namely, Pakistan Tehreek-e-Insaf (PTI), in Khyber Pakhtunkhwa, Pakistan Muslim League-Nawaz (PML-N), in Punjab, and Pakistan People’s Party Parliamentarians (PPPP), in Sindh, translated climate-related promises in their manifos to provincial-level green action between 2013 and 2018. The study uses a qualitative comparative design combining content analysis of the political party’s manifesto with semi-structured interviews of political leaders, bureaucrats and the civil society actors to cast an eye into the relationship between political incentive, institutional capability and environmental performance. Results show that there is a stark inter-provincial difference. Ecological sustainability At Punjab, political visibility was interpreted by green programmers instigated by PML -N at the cost of environmental sustainability, and at Sindh, PPP-led mangrove conservation had fragile institutional ownership and relied on donor funding. The Billion Tree Tsunami of PTI in Khyber Pakhtunkhwa achieved the international visibility because of the strong political-bureaucratic rapport and the well-developed control systems but the sustainability of the project, as well as its continuity, remains a problem. In all the instances inadequate monitoring processes, piece meal institutional duties and dependency on election cycles undermined policy effectiveness. This study shows that the relationship between political will, institutional framework, and donor involvement rather than the policy ambition shape subnational climate governance in Pakistan. The paper adds to the current body of work by connecting commitments of the manifesto and delivery of outcomes and promotes the need to institutionalize, cross-party structures to ensure lasting and effective climate action. The results have practical implication to the heightening accountability, sustainability, and environmental effects of the green projects in the federal developing states.